An Analysis of the Role of Cooperative Learning Approach on Students’ Character Building in English Learning - Dian Margaretha Enjelina Halawa; Elwin Piarawan Zebua; Afore Tahir Harefa; Riswan Zega (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study explores the role of cooperative learning methods, particularly the Learning Together model, in shaping student character at UPTD SMP Negeri 2 Gunungsitoli. The research employed a qualitative approach, collecting data through classroom observation of 22 eighth-grade students and interviews with an English teacher. The focus was on how cooperative learning fosters essential values such as responsibility, tolerance, collaboration, and effective communication, which are closely aligned with the dimensions of the Pancasila Student Profile. Findings reveal that the Learning Together model effectively enhances students’ social interactions, mutual respect, and willingness to participate actively in group discussions. It also promotes a sense of accountability by encouraging students to contribute ideas, support one another, and take shared responsibility for group outcomes. Beyond academic improvement, the model cultivates positive character traits that are necessary for holistic student development. Nevertheless, several challenges emerged during implementation. Some students displayed low self-confidence, while others struggled due to limited learning time and restricted access to teaching materials or supplementary resources. These barriers highlight the need for improved classroom support, extended learning opportunities, and diversified materials to optimize the effectiveness of cooperative learning. Overall, this research demonstrates that cooperative learning, when applied to English lessons, not only strengthens language skills but also nurtures character values essential for preparing students to meet future challenges. The study offers practical implications for educators, suggesting that balanced teaching strategies integrating academic competence with character development are vital within the Merdeka Curriculum framework. By addressing both cognitive and affective dimensions, teachers can create meaningful learning experiences that encourage students to grow as capable, responsible, and socially aware individuals.